Structural factor in bending testing of fivefold twinned nanowires revealed by finite element analysis. (12th October 2016) - Mets, Magnus; Antsov, Mikk; Zadin, Vahur; Dorogin, Leonid M; Aabloo, Alvo; Polyakov, Boris; Lõhmus, Rünno; Vlassov, Sergei
Abstract: In this study, we performed finite element method simulations to investigate the effect of the structure on the elastic response of Ag and Au nanowires (NWs) with a fivefold twinned crystal structure in bending tests. Two different models of a pentagonal NW were created: a 'uniform model' having an isotropic continuous structure and a 'segmented model' consisting of five anisotropic domains. Two asymmetrical mechanical test configurations were simulated: cantilevered beam bending and 3-point bending. The dimensions of the NW, the test configurations, as well as the force and the displacement ranges were based on the previously obtained experimental data. The results of the simulations demonstrated that the segmented model was stiffer than the uniform one in both of the bending tests. The effect was more pronounced for the cantilevered beam bending configuration. This fact should be taken into account in the interpretation of the increased measured Young's modulus of pentagonal NWs in comparison to the elasticity of the same material in bulk form.